2012
DOI: 10.1080/10410236.2011.636479
|View full text |Cite
|
Sign up to set email alerts
|

Public Discourses About Teenage Pregnancy: Disruption, Restoration, and Ideology

Abstract: Two recent incidents in the United States generated a wealth of public discourses about a particular reproductive health issue: adolescent childbearing. As the media, political pundits, and private citizens pondered the meaning of these events, they expressed viewpoints, explanations, and possible solutions in mass-mediated outlets. We examined the discourses communicated in such outlets to understand how public discussion of teenage pregnancy reveals ideological assumptions about reproductive health, ideal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Another qualitative study that explored low-income women's fertility expectations revealed similar messages low-income women receive about preventing their fertility (Bute & Jensen, 2010). Judy, a Caucasian (Bute, 2012) They-they just-they just seem like they just didn't want me to have any kids (laughs) at all. At all.…”
Section: Medicalization Of Infertilitymentioning
confidence: 96%
“…Another qualitative study that explored low-income women's fertility expectations revealed similar messages low-income women receive about preventing their fertility (Bute & Jensen, 2010). Judy, a Caucasian (Bute, 2012) They-they just-they just seem like they just didn't want me to have any kids (laughs) at all. At all.…”
Section: Medicalization Of Infertilitymentioning
confidence: 96%